Green Consumerism : an Eco-Friendly Behaviour Form Through The Green Product Consumption and Green Marketing - Handayani, Wiwik (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2017)
This research is referred to analyse the influence of consumer attitude of green product towards purchase intention. The consumer attitude of green product is a psychological tendencies that is expressed by evaluating a certain entity with some advantage or disadvantage considerations. The problem of this research is the low of cunsumer awareness to consume green product, because the lack to comprehend the importance of green product usage for health and eco-friendly. The purpose of this research is to test the influence of consumer attitude of green products towards purchase intention. Hypothesis testing using Partial Least Square (PLS). The result of analysis show that there is influence among consumer attitude of green product towards consumer purchase intention significantly.